Response Of Growth and Production of Red Chili to The Application of Trichoderma harzianum in Various Combinations of Planting Media - Usamah Rofi Robbani; Andi Masnang; Srikandi Srikandi (Universitas Nusa Bangsa, 2025)
Trichoderma harzianum has the ability as a decomposer organism and biological agent to control germination diseases that usually attack red chili plants. This study aims to determine the effectiveness of organic fertilizer given by T. harzianum on the productivity of red chili plants. The study consisted of eight treatments with four replications, namely treatment P0 (control), P1 (soil media + T. harzianum), P2 (soil medium + goat manure), P3 (soil media + manure + T. harzianum), P4 (soil media + compost), P5 (soil media + compost + T. harzianum), P6 (soil media + cocopeat), P7 (soil media + cocopeat + T. harzianum). The experimental design used was a completely randomized design (CRD). Parameters observed were plant height, number of leaves, flowering time, number of fruits, fruit length and fruit weight. The results showed that the enrichment treatment of organic fertilizer using T. harzianum had a very significant effect on plant height and number of leaves. Treatment using T. harzianum affected the height of red chili plants at the age of 14, 21, 28, 35 and 42 days after planting (DAP). The number of leaves was significantly different at the age of 21, 28, 35, and 42 DAP. The application of T. harzianum in goat manure had a very significant effect on the number of fruits, fruit length, and fruit weight. The best treatment was P3 treatment, namely soil added with goat manure in a ratio of 2:1 and T. harzianum 12 g had a very significant effect on plants, number of leaves, number of fruits, fruit weight, and fruit length of red chilies.